Islamic Education and Social Transformation: A Sociological Analysis of Faith-Based Education in Indonesia - Nur Khasanah; Abdul Khobir; Achmad Irwan Hamzani; Havis Aravik (Penerbit dan Percetakan CV. Picmotiv, 2026)
Islamic education in Indonesia operates within a highly plural society and continues to adapt to rapid social change. Despite its traditional roots, pesantren and madrasah remain central to shaping moral formation, communal resilience, and inclusive religious identity. This study examines how Islamic education contributes to social transformation and what socio-theological values emerge from faith-based practice. Using qualitative library research and thematic analysis of recent peer-reviewed literature, the study integrates sociological perspectives with theological insights to interpret how institutions embed Qur’anic–Hadith principles in educational life. Findings show that pesantren safeguard tradition while cultivating moderation, solidarity, and moral literacy, whereas madrasah combine Islamic studies with modern sciences to strengthen critical thinking and civic responsibility. The study’s originality lies in its interdisciplinary socio-theological approach, revealing that spiritual values such as ʿadl, raḥmah, ukhūwah, and taʿāwun shape not only personal ethics but also social behavior, interfaith engagement, and ecological consciousness. These insights highlight Islamic education’s capacity to negotiate globalization, technology, and secular pressures without diminishing theological depth. The research implies the need for value-based curricula, leadership development, enhanced digital literacy, and expanded interfaith initiatives to sustain a moderate and future-oriented model of Islamic education.